2021
DOI: 10.1177/21582440211052932
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Pre-service Pre-primary EFL Teacher Beliefs about Teaching English to Very Young Learners: A Macau Case Study

Abstract: Research on the beliefs of pre-service and in-service English teachers at the primary, secondary, and tertiary levels has provided useful knowledge to teacher education curriculum designers. However, the beliefs of pre-service pre-primary English as a foreign language (EFL) teachers have not been addressed. Thus, a case study was conducted in one pre-primary education program at a public university in the Macau Special Administrative Region of China. Data was collected by providing participants ( N = 63) a wri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 53 publications
(76 reference statements)
0
4
0
Order By: Relevance
“…The similar point of views leads the mutual understanding to reach the aim of learning. Therefore, many studies in EFL context have investigated the teachers' perception (Alghasab, 2020;Bsharat et al, 2021;Ćirković-Miladinović and Dimitrijević, 2020;Luan et., 2020;Millán Librado & Santos, 2020;;Reynolds et al, 2021) and students' perceptions (Abdelrady et al, 2022;Abdullah, 2020;Cabrera-Solano et al, 2019;Fithriani et al, 2019;Hussain Al-Qahtani, 2019;Ika Dhamayanti, 2021;Karimian Shirejini & Shirejeni, 2020;Klimova & Polakova, 2020;Millá n Librado & Santos, 2020;Roos & Nicholas, 2019;Sheybani, 2019;Soria et al, 2020;Pishghadam et al, 2021;Vattøy & Smith, 2019;Wallace & Leong, 2020;Wang et al, 2019). The respondent and participants used in the previous studies of EFL are also varied such as university or college students (Abdullah, 2020;Alghasab, 2020;Hussain Al-Qahtani, 2019;Karimian Shirejini & Shirejeni, 2020, Klimova & Polakova, 2020Luan et al, 2020;Reynolds et al, 2021;Wang et al, 2019), the respondent from senior high students (Abdelrady et al, 2022;Ika Dhamayanti, 2021;Hadj Said & Al-Jamal, 2018), and the respondent from elementary school (Bsharat et al, 2021;Cabrera-Solano et al, 2019;Ćirković-Miladinović and Dimitrijević, 2020;Gutierrez Arviz...…”
Section: Introductionmentioning
confidence: 99%
“…The similar point of views leads the mutual understanding to reach the aim of learning. Therefore, many studies in EFL context have investigated the teachers' perception (Alghasab, 2020;Bsharat et al, 2021;Ćirković-Miladinović and Dimitrijević, 2020;Luan et., 2020;Millán Librado & Santos, 2020;;Reynolds et al, 2021) and students' perceptions (Abdelrady et al, 2022;Abdullah, 2020;Cabrera-Solano et al, 2019;Fithriani et al, 2019;Hussain Al-Qahtani, 2019;Ika Dhamayanti, 2021;Karimian Shirejini & Shirejeni, 2020;Klimova & Polakova, 2020;Millá n Librado & Santos, 2020;Roos & Nicholas, 2019;Sheybani, 2019;Soria et al, 2020;Pishghadam et al, 2021;Vattøy & Smith, 2019;Wallace & Leong, 2020;Wang et al, 2019). The respondent and participants used in the previous studies of EFL are also varied such as university or college students (Abdullah, 2020;Alghasab, 2020;Hussain Al-Qahtani, 2019;Karimian Shirejini & Shirejeni, 2020, Klimova & Polakova, 2020Luan et al, 2020;Reynolds et al, 2021;Wang et al, 2019), the respondent from senior high students (Abdelrady et al, 2022;Ika Dhamayanti, 2021;Hadj Said & Al-Jamal, 2018), and the respondent from elementary school (Bsharat et al, 2021;Cabrera-Solano et al, 2019;Ćirković-Miladinović and Dimitrijević, 2020;Gutierrez Arviz...…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with a study by Sikki et al (2013), which found 51% of Indonesia preschool teachers never attended ELT training. Solution to this problem is to design a more effective and comprehensive training programme to ensure improved performance (Reynolds et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In general, a “belief” has four common features, including that it “may be consciously or unconsciously held,” “is evaluative in that it is accepted as true by the individual,” “is imbued with emotive commitment,” and “serves as a guide to thought and behavior” ([ 13 ], p.186). In particular, teacher beliefs play an essential role in many aspects of teaching and learning, especially “beliefs about teachers performing tasks and the nature of knowledge” ([ 14 ], p. 2). Teacher beliefs have been shown to be influenced by a teacher’s personal experience [ 15 , 16 ], teaching experience [ 16 ], educational background [ 17 ], and colleague support [ 16 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Teacher beliefs have been shown to be influenced by a teacher’s personal experience [ 15 , 16 ], teaching experience [ 16 ], educational background [ 17 ], and colleague support [ 16 ]. Moreover, the literature has provided insights into teacher beliefs concerning teaching practice [ 18 , 19 , 20 ], teacher education [ 21 , 22 , 23 , 24 ], learning experience [ 25 ], curriculum design [ 14 , 26 ] parent involvement [ 27 ], learner autonomy [ 13 ], and corrective feedback [ 28 , 29 ]. Researchers have also suggested that there is a strong relationship between teacher beliefs and their teaching practice in EFL classrooms [ 1 , 13 , 30 , 31 ].…”
Section: Literature Reviewmentioning
confidence: 99%